2019
DOI: 10.1097/iae.0000000000002125
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Characteristics of Male Patients With RPGR-Associated Retinal Dystrophies

Abstract: Based on best-corrected visual acuity survival probabilities, the intervention window for gene therapy for RPGR-associated retinal dystrophies is relatively broad in patients with RP. RPGR-ORF15 mutations were associated with COD/CORD and with a more severe phenotype in RP. High myopia is a risk factor for faster best-corrected visual acuity decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
104
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(111 citation statements)
references
References 41 publications
7
104
0
Order By: Relevance
“…A hyper-AF ring was found in six out of nine patients, including the CRD patient. Previous studies have shown that the hyper-AF ring correlates with the presence of the EZ band and demarcates the transition between healthy and affected retina [2,22,23]. The constriction of this hyper-AF ring in RP indicates disease progression, whereas, conversely, the expansion of the hyper-AF ring in CRD patients suggests disease progression [2,24].…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…A hyper-AF ring was found in six out of nine patients, including the CRD patient. Previous studies have shown that the hyper-AF ring correlates with the presence of the EZ band and demarcates the transition between healthy and affected retina [2,22,23]. The constriction of this hyper-AF ring in RP indicates disease progression, whereas, conversely, the expansion of the hyper-AF ring in CRD patients suggests disease progression [2,24].…”
Section: Discussionmentioning
confidence: 93%
“…Patients therefore typically present with symptoms of nyctalopia and peripheral visual field constriction, prior to symptoms of central vision loss. X-linked RP (XLRP) accounts for 5%-15% of all RP cases and is recognized as one of the most severe forms of RP [2,3]. Mutations in the RPGR gene are responsible for 70%-90% of all XLRP cases [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations